[Potential construction spot for a "library addition" on Cal Poly's campus] - P. K. Phillips::::::photographer::: (1970)
A potential construction spot for a "library addition" on Cal Poly's campus. The site study conducted for this location is titled "Site Study 5." If used, this addition would have taken two phases and placed the building behind the Administration Building (Building 1) and the Science building (Building 52).